Dielectrophoresis of spermatozoa in viscoelastic medium - Koh, James Boon Yong (2015)
Knowledge of spermatozoa motility is important in selecting suitable spermatozoa for assisted reproduction procedures. By considering the internal sliding force within an active filament, its shape in a viscoelastic Oldroyd-B fluid subjected to nonuniform electric field is presented. The resulting velocity is a function of the beating pattern and DEP force, which is dependent on the spermatozoon's morphology as well as the gradient of the mean square electric field. Finally, the velocities of the X- and Y-spermatozoa are compared under various conditions of nonuniform electric field and viscoelasticity of the medium. The presence of DEP force alters their velocities to different extents, giving an 84% level of confidence for selecting spermatozoon that contains the chromosome leading to a female. Therefore, a nonuniform electric field can be used not only to sort and select spermatozoa of desired morphology, but also for gender selection. Moreover, we found that sorting in a viscoelastic fluid medium is more effective as the effect of DEP on the spermatozoa velocity is enhanced by an order of magnitude.